In-situ characterization of heterogeneous catalysts using time-resolved X-ray diffraction - Rodriguez, José; Hanson, Jonathan (Ciencia, 1970)
Time-resolved x-ray diffraction (XRD) has emerged as a powerful technique for studying the behavior of heterogeneous catalysts (metal oxides, sulfides, carbides, phosphides. zeolites, etc) in-situ during reaction conditions. The technique can identify the active phase of a heterogeneous catalyst and how its structure changes after interacting with the reactants and products (80 K ï€¼ T ï€¼ 1200 K; Pï€¼ 50 atm). In this article, we review a series of recent works that use time-resolved XRD for studying the reduction/activation of oxide catalysts (CuO, Cu2O, CuO/CeO2, Ce1-x Cx Cux O2, NiO, NiMoO4, CoMoO4). These studies illustrate the important role played by O vacancies in the mechanism for reduction of an oxide. The phenomenological kinetic models frequently used in the description of the reduction process can be useful, but a more relevant aspect is the initial production of active sites for the rapid dissociation of H2. This done can lead to the appearance of “induction periods” in the reaction kinetics and the possibility for autocatalysis. In-situ studies for the water-gas shift reaction on CuO, Cu2O, CuO/CeO2 and Ce1-x Cux O2, catalysts show that Cuº is the active species of copper (i.e. no Cu+1 or CU+2 cations), but interactions with the oxide support are necessary in order to obtain high catalytic activity.